The comparison of antioxidant and bioactive compound in fresh pineapple and pineapple powder: article / Inun Hazwani khairuddin and Syafiza Abd Hashib - khairuddin, Inun Hazwani; Abd Hashib, Syafiza (2017)
The aims of this study were to determined the antioxidant and bioactive compound of fresh pineapple between pineapple powder and to evaluate the antioxidant and bioactive compound of fresh pineapple. Ascorbic acid, total phenolic compound, total flavonoid and 2,2-diphenyl-1-picrylhydrazil (DPPH Assay) were analyzed using morris pineapple flesh. The ascorbic acids, total phenolic compound and total flavonoid in the morris pineapple flesh is higher rather than pineapple powder. The proximate and physiochemical properties showed good quality and increased solubility of pineapple powder compared to the fresh pineapple. Based on experiment, the highest antioxidant is obtained when 100% of extracted methanol in fresh pineapple was 65mg/L rather than pineapple powder was 53mg/L. So, overall the spray dried of pineapple may be a good source of natural antioxidants and profoundly increase the uses of pineapple in value added processing and dietary intake.